(untitled) (Global Journal of Management and Business Research, 2016)
This study is focused on investigating the collision of leverage and liquidity on banks’ profitability of the conventional banking sector of Pakistan. The major indicators of the financial performance of corporate entities are liquidity, leverage and profitability. Two independent variables i.e. leverage and liquidity were taken into consideration to find out the impact on dependent variable, i.e. bank’s profitability. The sample chosen for this certain study is the three famous Pakistani conventional banks. The 10 years data was collected from the "Annual Reports and Accounts" of the 3 banks, i.e. Faysal Bank, Alfalah and MCB. Regression, correlation and tstatistics are used for the examination of hypothesis. The research results states that liquidity is insignificantly positively related with profitability and leverage is significantly negatively correlated with profitability. Focusing on liquidity and profitability will help banks to enhance their growth.